pCO2 values in asphyxiated infants under therapeutic hypothermia after tailored respiratory management: a retrospective cohort study - Serrao, Francesca; Tiberi, Eloisa; Verdolotti, Tommaso; Romeo, Domenico Marco Maurizio; Corsello, Mirta; Pede, Elisa; Cota, Francesco; Costa, Simonetta; Gallini, Francesca; Colosimo, Cesare; Mercuri, Eugenio Maria; Vento, Giovanni (Frontiers in Pediatrics, 2024)
Background: Hypoxic-ischemic encephalopathy (HIE) represents one of the major causes of neonatal death and long-term neurological disability. Both hypoxic ischemic insult and therapeutic hypothermia (TH) can affect respiratory function. There is currently no evidence on the optimal respiratory management in these infants. Methods: This is a retrospective cohort study examining newborns with HIE treated with TH between January 2015 and September 2020. The study population was divided into two groups based on different respiratory assistance during TH: spontaneous breathing (Group A) or mechanical ventilation (Group B). The primary outcome of the study was the mean pCO2 ± SD evaluation during the TH among ventilated and not ventilated asphyxiated infants. Secondary outcome was the correlation between the respiratory strategy and the short-term neurologic outcomes according to Rutherford et al. MRI score. Results: 126 newborns were enrolled, 75 in Group A and 51 in Group B. Respiratory management was individualized and volume guarantee (VG) ventilation was the first choice in ventilated infants. Group B infants showed more severe condition at birth. During TH, ventilated infants showed optimal mean pCO2 comparable with those spontaneously breathing (40.6 mmHg vs 42.3 mmHg respectively, p 0.091) with no significant difference in pCO2 standard deviation between (7.7 mmHg vs 8.1 mmHg respectively, p 0.522). Also mean pH, pH standard deviation, mean pO2, pO2 standard deviation and mean respiratory rate did not differ between the groups. MRI pattern of brain injury predictive of abnormal neurodevelopmental outcome were similar in the two groups. The logistic regression analysis demonstrated that only cordonal arterial pH affect MRI lesions related to poor neurodevelopmental outcome (OR 1.505; CI 95% 1.069-2.117). Conclusions: Infants cooled after HIE should receive individualized respiratory management, not necessarily involving intubation. In those infants requiring mechanical ventilation, volume targeted strategy seemed to be effective in maintaining stable blood gas levels. Short-term neurological outcomes appeared comparable in ventilated and nonventilated infants.